CELLULAR AND HUMORAL INDICES OF IMMUNITY IN PATIENTS WITH LOCAL FORMS OF DIPHTHERIA AND PURULENT INFLAMATOVY PROCESSES OF TONSILS AND THEIR DIFFERENTIAL DIAGNOSTIC IMPORTANCE - Polukchy, O.K. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
77 patients with local forms of diphtheria of oralpharynx and 49 patients with tonsillitis have been examined. Cellular and humoral indices of blood immunity have been studied/ It is established that alterations of immunity in the patients with diphtheria and tonsillitis are of different purposefulness. This fact enables to use these indices for differential diagnosis.